Reply to Kiely et al.: Comment on: "Biological background of block periodized endurance training: A review" - Issurin, B. B. (Sports Medicine, 2019)
First, I would like to express my gratitude to Kiely et al. [1] for a further opportunity to continue consideration of the block periodization (BP) concept and its practical implementation in the journal Sports Medicine. I appreciate my opponents` attention to the topic and reply in the order of the critical items appearing in the letter by Kiely et al. [1].